Effects of Forest Restoration Techniques on Community Diversity and Aboveground Biomass on Area Affected by Mining Tailings in Mariana, Southeastern Brazil - Campanharo, Ítalo Favoreto; Martins, Sebastião Venâncio; Villa, Pedro Manuel; Kruschewsky, Gabriel Correa; Dias, Andreia Aparecida; Nabeta, Fabio Haruki (Research in Ecology, 2020)
Currently there is an urgent and special attention in actions to restore tropical forests. In this study, we evaluated the effect of different restoration methods on aboveground biomass (AGB) stock, tree community diversity and structure, in areas affected by the Fundão tailings dam collapse in Mariana, Minas Gerais state, Brazil. We measured and compiled data of the AGB, community diversity and structure attributes in 36 plots distributed in six restoration treatments and six replicas: planting of native tree seedlings with fertilization and pH correction (PSf) and without fertilization and pH correction (PS); seeding of native trees with fertilization and pH correction (SDf) and without fertilization and pH correction (SD); natural regeneration with fertilization and pH correction (NRf) and without fertilization and pH correction (NR). No significant differences in substrate properties and AGB between treatments. Although biomass storage between treatments was not statistically different, there is a clear pattern showing higher values active restoration method. The Pielou index ranged from 0.520 (SDf) to 0.943 (NR), except for SDf all the others treatments had values higher than 0.76. This result suggests floristic heterogeneity, without ecological dominance in the plant community. Overall, active restoration had important implications for the forest restoration where natural regeneration is limited.